Serial Cases of Combining ESWL and ERCP Procedures in Management Chronic Pancreatitis and Difficult Bile Duct Stones - Achmad Fauzi; Nur Rasyid; Ari Fahrial Syam; Murdani Abdullah; Dadang Makmun; Marcellus Simadibrata; Chudahman Manan; Abdul Aziz Rani; Daldiyono Daldiyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2009)
Extracorporeal shock wave lithotripsy (ESWL) has an established role in the management of pancreaticductalcalculiandasfurthertreatmentmodalityforlargeordifficultcomplicatedcommon bile duct(CBD)stones. Combinedwithminimally invasive endoscopic procedure suchasendoscopic retrogradecholangio-pancreatography(ERCP),it has replaced open surgeryas theinitial form of therapy. ESWL has also proved to bean effective therapyin treating intrahepaticstones that are refractory toroutine endoscopic extraction.Inthese serialcaseswe presentthree caseswhichusing combinedESWLandERCP procedurestotreatchronicpancreatitispainandgiantCBDstonethat presentinggoodresultsonfollowupwithoutanycomplication.  Keywords:ESWL, ERCP,chronicpancreatitis, CBDstone